Purchases of Fruit and Vegetables for at Home Consumption During COVID-19 in the UK: Trends and Determinants - Revoredo-Giha, Cesar; Russo, Carlo; Twum, Edward Kyei (Frontiers in Nutrition, 2022)
This paper addresses the issue of fruit and vegetable consumption in the UK during the pandemics. The study is motivated by the importance of fruit and vegetables for human nutrition, health and reduction of population obesity, especially in the UK where per capita consumption is still below recommended levels. A rich panel dataset was used reporting actual shopping places and quarterly expenditure for at-home consumption of fruit and vegetable purchases of 12,492 households in years 2019 and 2020. The unique dataset allowed us to compare expenditure for fruit and vegetables before and after the COVID-19 outbreak and to identify the main drivers of changes in consumption. Regression analysis found that expenditure increased approximately 3 per cent less than what expected given the overall increase in the numbers of at-home meals during lockdown. Also, online shopping was associated with an increase in expenditure for fruit and vegetable, suggesting that online shopping helped keeping a balanced diet during the pandemics. However, the expenditure for processed products grew more than the one for fresh products, resulting a reduction of the relative share of the latter and possible deterioration of the diet quality.